STUDI AWAL ROADMAP PENELITIAN DAN PKM DOSEN FKIP UNTAN TAHUN 2019-2021 - Riyanti, Dwi (Universitas Tanjungpura, 2023)
This study aims to explore the preliminary data about the research and community service roadmaps of study programs at the Teacher Training and Education Faculty (FKIP), Universitas Tanjungpura (Untan). This research is intended to identify how lecturers in each of the study programs at FKIP Untan conducted research and community services in the last three years (2019-2021). The data collection for this study was carried out by tracing research topics and lecturers' community services taken from the recapitulation of research and lecturers' community services in the last three years (2019-2021) from the finance department. The results of the research and community service data analysis over the previous three years (2019-2021) show that the research and community services of lecturers in the study programs at FKIP Untan are following the field of the study programs. However, some of the lecturers' research is not following the area of the Study Programs. The results of the analysis also indicate that all research and lecturers' community service topics are based on the research and community service roadmap of FKIP Untan